Clinical analysis of neoadjuvant chemotherapy in patients with advanced vulvar cancer: A STROBE-compliant article. Issue 34 (August 2018) - Niu, Yizhen; Yin, Rutie; Wang, Danqing; Li, Qingli; Gao, Xiu; Huang, Meimei
Abstract : Abstract: To investigate the effect of neoadjuvant chemotherapy in patients with advanced vulvar cancer and to provide references for clinical treatment. Clinical and pathological data of 12 patients with advanced vulvar carcinoma were collected. The response and operability rates, adverse effects, and prognosis of neoadjuvant chemotherapy were retrospectively analyzed. The mean patient age was 45.8 (range 26–69) years. Among 12 patients, 9 underwent treatment with bleomycin and cisplatin with or without vincristine. The overall response rate was 67%. Five patients (56%) experienced grade 1 or 2 bone marrow suppression or gastrointestinal reactions. Seven patients (78%) underwent radical surgery. The mean overall survival time was 34.1 (range 3–69) months, the mean progression free survival time was 26 (range 3–69) months, and the 1-year survival rate was 83%. The other 3 patients received combined paclitaxel and cisplatin treatment. The overall response rate was 67%. All 3 patients (100%) experienced grade 2 hair loss or anemia and 2 of them (67%) underwent radical vulvectomy. The mean overall survival time was 11.7 (range 5–15) months, the mean progression free survival time was 7.7 (range 3–15) months and the 1-year survival rate was 100%. Time to overall survival and progression free survival were not significantly different between the 2 groups ( P  = .46 and P  = .39). Owing to their high overall response rate and tolerable adverse effects, either bleomycin–cisplatin-based or paclitaxel-based neoadjuvant chemotherapy regimen can be considered a therapeutic option for advanced vulvar cancer.